Al / SiC composite material with continuously distributed metals and preparation method of Al / SiC composite material

Through the combination of digital light treatment and gel injection molding, a ceramic body with flexible structure was designed, and a metal-continuous distribution Al/SiC composite material was obtained through impregnation technology, which solved the problem of uneven soft phase distribution in traditional composite materials. , improves the toughness and application range of materials.

CN119433325APending Publication Date: 2025-02-14JILIN UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411640145.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Traditional cermet composites have uneven distribution, local loss or discontinuity of soft phases in microstructure design, resulting in reduced mechanical properties and increased risk of stress concentration.

Method used

Using a combination of digital light treatment and gel injection molding, ceramic blanks are reversed by calcium carbonate, ceramic blanks with flexible structure and shape are designed, and Al/SiC composite materials with continuous metal distribution are obtained through impregnation technology. .

Benefits of technology

It effectively solves the problem of soft phase discontinuity inside the composite material, improves the toughness of the composite material, avoids stress concentration, and expands the range of prepared configurations, reducing the manufacturing cost of complex configuration composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433325A_ABST
    Figure CN119433325A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of composite materials, and provides an Al / SiC composite material with metal continuously distributed, the metal Al phase is continuously distributed, and SiC-rich ceramic columns are separately distributed; the SiC-rich ceramic stand column is composed of A1 and SiC particles together, and a network structure with soft phases surrounding hard phases and interpenetrating soft phases is formed. The plane figure of the SiC-rich ceramic upright post is one of a circle, a rectangle, a triangle, a star, a honeycomb, a concave honeycomb, a broken line shape and a wave shape; the volume fraction of ceramic in the SiC-rich ceramic stand column is 25-60 vol.%. The invention further provides a preparation method of the Al / SiC composite material with the metal continuously distributed. According to the preparation method, digital light treatment and gel casting are combined, a ceramic blank reverse mold is constructed by using calcium carbonate, the design is flexible and changeable, and the metal ceramic composite material with continuously distributed metal is obtained through an infiltration technology, so that a continuous soft phase can effectively disperse external loads, stress concentration is avoided, and the toughness of the composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and in particular relates to an Al / SiC composite material with continuous metal distribution and a preparation method thereof. Background Art

[0002] Lightweight, strong materials with good energy absorption characteristics are highly favored in practical engineering applications. In this context, metal-ceramic composites, as a new type of material, can more effectively utilize the advantages of their components. The complex structures formed by biological evolution in nature provide rich inspiration for the design of artificial materials, especially in the microstructure design of metal-ceramic composites. For example, natural materials such as pearl oysters achieve synergistic effects through their unique component structures. The combination of hard phase load-bearing and soft phase energy absorption enables them to exhibit mechanical responses far beyond the conventional mixing law. However, traditional processing methods such as manual lamination and injection molding often lead to uneven distribution of the soft phase, and even localized missing or discontinuous phenomena. This unevenness not only significantly reduces the mechanical properties of the composite material, but also increases the potential risk of stress concentration.

[0003] Melt infiltration technology is an effective method to obtain a continuous metal phase. It is based on the penetration of molten metal into the open pores of a porous support under the action of capillary force or external pressure. After the metal phase solidifies, a metal-ceramic composite material is formed. The usual preparation process is to first form a ceramic skeleton and then use molten alloy to infiltrate the ceramic body. Although traditional ceramic forming methods, such as adding pore-forming agents, foaming and freeze casting, can produce a ceramic skeleton with a network structure, they generally have the following problems: the ceramic phase is continuous while the metal phase is discontinuous or incompletely continuous, and the shape or structure of the product is relatively simple. These problems limit the toughness of the composite material and its application. Therefore, a novel forming method is urgently needed to overcome these limitations. Summary of the invention

[0004] The purpose of the embodiments of the present invention is to provide an Al / SiC composite material with continuously distributed metal, aiming to solve the problems existing in the above-mentioned background technology.

[0005] The embodiment of the present invention is implemented as follows: an Al / SiC composite material with continuous metal distribution, wherein the metal Al phase is continuously distributed and the SiC-rich ceramic pillars are isolatedly distributed; The SiC-rich ceramic pillars are composed of Al and SiC particles, forming a network structure in which the soft phase surrounds the hard phase and the soft phases interpenetrate each other; The plane shape of the SiC-rich ceramic column is one of a circle, a rectangle, a triangle, a star, a honeycomb, a concave honeycomb, a broken line, and a wave; The ceramic volume fraction in the SiC-rich ceramic column is 25-60 vol.%.

[0006] Another object of an embodiment of the present invention is to provide a method for preparing an Al / SiC composite material with continuous metal distribution, comprising the following steps: (1) preparing a photocurable resin composed of a resin monomer, a diluent and a photoinitiator; wherein, by volume percentage, the resin monomer is 50-65%, the diluent is 35-50%, and the sum of the volume percentages of the resin monomer and the diluent is 100%; and a photoinitiator is additionally added, the amount of which, by mass percentage, accounts for 2-5% of the total mass of the resin monomer and the diluent; (2) mixing calcium carbonate powder, photocurable resin and dispersant by ball milling into a printing slurry; wherein, by volume percentage, the calcium carbonate powder is 20-40%, the photocurable resin is 80-60%, and the sum of the volume percentages of the calcium carbonate powder and the photocurable resin is 100%; and additionally adding a dispersant BYK111, the amount of which by mass percentage accounts for 0.5-1.5% of the calcium carbonate powder; (3) Using modeling software to build a calcium carbonate resin model, using digital light processing technology to print the printing slurry into shape, and using an organic solvent to clean the calcium carbonate resin model to remove excess slurry; (4) preparing a gel slurry formed by ball-milling a SiC ceramic powder, deionized water, an initiator, a gel resin, a sintering aid and a dispersant; wherein, by volume percentage, 20-50% SiC ceramic powder, 80-50% solvent, the sum of the volume percentages of SiC ceramic powder and solvent is 100%, and the solvent comprises 90-60% deionized water and 10-40% gel resin; a sintering aid is additionally added, the amount of which is 1-10% of the SiC ceramic powder by mass percentage; a dispersant is additionally added, the amount of which is 0.2-1.0% of the SiC ceramic powder by mass percentage; an initiator is additionally added, the amount of which is 0.05-0.2% of the gel resin by mass percentage; (5) pouring the gel slurry into a custom mold, pressing the calcium carbonate resin model into the gel slurry, then placing the mold in a sealed metal can and evacuating the can to remove bubbles in the slurry, and then introducing high-pressure gas to completely fill the calcium carbonate resin model with the slurry; (6) placing the mold containing the gel slurry and the calcium carbonate resin model on a heating platform, and removing the mold after the gel is solidified to obtain a SiC blank; (7) drying the solidified SiC body to remove residual moisture, then removing the resin through a degreasing process, and then obtaining a body according to a sintering process, and immersing the body in a hydrochloric acid solution to remove residual calcium oxide, thereby obtaining a SiC isolated column body with continuous pores; (8) The SiC isolated column blank with continuous pores is dried to obtain a SiC ceramic skeleton, into which liquid metal aluminum or aluminum alloy is injected using a pressure infiltration technique to obtain an Al / SiC composite material with continuous metal distribution.

[0007] Preferably, in step (1), the resin monomer is an acrylate monomer or a vinyl ether monomer; The diluent is one or more of pentaerythritol triacrylate, hydroxyethyl methacrylate, camphene, glycerol, tert-butyl alcohol and camphor; The photoinitiator is one or more of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone and 2-isopropylthioxanthone; The mixing method is heating magnetic stirring, the rotation speed is 100-400 rpm, the heating temperature is 25-50°C, and the stirring time is 20-60 min.

[0008] Preferably, in step (3), the plane shape of the SiC-rich ceramic column is one of a circle, a rectangle, a triangle, a star, a honeycomb, a concave honeycomb, a broken line, and a wave. The top and bottom surfaces of the calcium carbonate resin model are designed with circular holes for reserving channels for the slurry to flow into during the gel injection molding process, and forming connections between the columns at the top and bottom.

[0009] Preferably, in step (4), the gel resin is a mixture of N,N-dimethylacrylamide and N,N'-methylenebisacrylamide, and the volume ratio of N,N-dimethylacrylamide to N,N'-methylenebisacrylamide is 6-15:1; The sintering aid is a mixture of Al2O3 and MgO, and the mass ratio of Al2O3 to MgO is 2-8:1; The dispersant is CMC-Na; The initiator is ammonium persulfate.

[0010] Preferably, in step (6), the curing operation is: keeping the temperature between 30-70° C. on a heating platform for 10-60 min.

[0011] Preferably, in step (7), the drying operation is: drying in a vacuum drying oven at a vacuum degree of 50-250 Pa for 12-24 h; The degreasing operation is: heating to 450-600°C at a heating rate of 0.1-2°C / min, wherein the heating rate from 350°C to 450°C is 0.1-0.5°C / min; The sintering operation is: heating to 1000-1300°C at a heating rate of 0.5-5°C / min, wherein the heating rate from 650°C to 750°C is 0.5-1°C / min.

[0012] Preferably, in step (8), the drying operation is: heating to 200-400°C at a heating rate of 1-10°C / min, keeping the temperature for 30-120 min, and then cooling to room temperature at a cooling rate of 2-10°C / min; The pressure infiltration technology is specifically as follows: placing a SiC ceramic skeleton into an alumina crucible, placing an Al or Al alloy block on top of the SiC ceramic skeleton, and then placing the crucible into an infiltration furnace; evacuating the infiltration furnace to below 50 Pa, heating the furnace to 700-850°C at a heating rate of 5-10°C / min, keeping the temperature for 0-30 min, and introducing high-purity argon gas into the vacuum furnace to 1-5 MPa; and then cooling the furnace to room temperature at a cooling rate of 5-10°C / min.

[0013] An Al / SiC composite material method with continuous metal distribution provided in an embodiment of the present invention adopts a combination of digital light processing and gel injection molding, and uses calcium carbonate to construct a ceramic body reverse mold to prepare a ceramic body with flexible and changeable structure and shape design. A metal-ceramic composite material with continuous metal distribution can also be obtained through infiltration technology. The preparation method effectively solves the problem of discontinuity of the soft phase inside the composite material under the traditional manufacturing method, so that the continuous soft phase can effectively disperse the external load, avoid stress concentration, and improve the toughness of the composite material; In addition, the embodiments of the present invention also effectively solve the problems of collapse and bonding of isolated columns during post-processing by designing a special connection method between isolated columns, thereby expanding the range of preparable configurations; optimizing the preparation process, reducing the manufacturing cost of composite materials with complex configurations, and having a wide range of applicable materials, showing good universality. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 A flow chart of a method for preparing an Al / SiC composite material with continuous metal distribution provided by an embodiment of the present invention; Figure 2 Macroscopic photos of calcium carbonate resin molds provided in Examples 1-3 of the present invention (a is the circular column calcium carbonate resin model of Example 1, b is the concave honeycomb column calcium carbonate resin model of Example 2, and c is the broken line column calcium carbonate resin model of Example 3); Figure 3Macroscopic photos of SiC ceramic skeletons provided for Examples 1-3 of the present invention (a is the circular column SiC ceramic skeleton of Example 1, b is the concave honeycomb column SiC ceramic skeleton of Example 2, and c is the zigzag column SiC ceramic skeleton of Example 3); Figure 4 These are photos of the macroscopic and microscopic structures of the composite material provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0015] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0016] An Al / SiC composite material with continuous metal distribution, the preparation method thereof is as follows Figure 1 As shown, the specific steps include: (1) Using magnetic stirring, the resin monomer, diluent and photoinitiator are mixed to prepare a photocurable resin, the rotation speed is 100-400 rpm, the heating temperature is 25-50 °C, and the stirring time is 20-60 min; Wherein, by volume percentage, 50-65% of the resin monomer, 35-50% of the diluent, the sum of the volume percentages of the resin monomer and the diluent is 100%; additionally, a photoinitiator is added, and the amount added by mass percentage accounts for 2-5% of the total mass of the resin monomer and the diluent; The resin monomer is one or more of an acrylate monomer or a vinyl ether; the diluent is one or more of pentaerythritol triacrylate, hydroxyethyl methacrylate, camphene, glycerol, tert-butyl alcohol and camphor; the photoinitiator is one or more of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone and 2-isopropylthioxanthone; (2) ball-milling the calcium carbonate powder, the photocurable resin and the dispersant into a printing slurry, with a ball-milling speed of 800-1200 rpm, a ball-to-material ratio of (2-5):1, and a ball-milling time of 10-60 min; Wherein, by volume percentage, 20-40% calcium carbonate powder, 80-60% photocurable resin, the sum of the volume percentages of calcium carbonate powder and photocurable resin is 100%; additional dispersant BYK111 is added, and the added amount by mass percentage accounts for 0.5%-1.5% of the calcium carbonate powder; (3) The calcium carbonate resin printing model was designed using modeling software, and circular holes with a diameter of about half the side length were designed on the top and bottom surfaces of the model. The purpose of these holes was to reserve channels for the slurry to flow into the model during gel injection molding, thereby forming connections between the columns at the top and bottom. The calcium carbonate resin slurry was printed using digital light processing technology, and the process parameters used were: layer thickness 20-80 μm, first layer exposure intensity 19-44 mW / cm 2 , first layer exposure time 2-8 s; normal layer exposure intensity 5-25 mW / cm 2 , normal layer exposure time 0.5-4 s; first layer number 2-8 layers; the plane graphics of the printed structure inside the calcium carbonate resin mold include but are not limited to triangle, rectangle, honeycomb, concave honeycomb, circle, broken line, and wave; use organic solvent divalent ester to clean it, the method is ultrasonic cleaning, the cleaning time is 5 min, and the number of times is 2; (4) using a planetary ball mill to prepare a gel slurry by ball milling SiC powder, solvent (deionized water and gel resin), initiator ammonium persulfate, dispersant CMC-Na and sintering aids (Al2O3 and MgO), the ball milling speed is 100 rpm-300 rpm, the ball-to-material ratio is (0.5-1.5):1, and the ball milling time is 5-15 h; Wherein, by volume percentage, 20-50% ceramic powder, 80-50% solvent (including 90-60% deionized water and 10-40% gel resin, the volume ratio of N, N-dimethyl acrylamide to N, N'-methylene bis acrylamide in the gel resin is 6-15:1), and the sum of the volume percentages of ceramic powder and solvent is 100%; the amount of sintering aid (Al2O3 and MgO, the mass ratio is 2-8:1) added accounts for 1-10% of the ceramic powder by mass percentage, the amount of additional dispersant CMC-Na added accounts for 0.2-1.0% of the ceramic powder by mass percentage, and the amount of additional initiator ammonium persulfate added accounts for 0.05-0.2% of the gel resin by mass percentage; (5) pouring the gel slurry into a custom mold, pressing the calcium carbonate resin mold into the gel slurry, then placing the gel mold in a sealed metal can and evacuating the can to remove bubbles in the slurry, and then introducing 0.2-0.4 MPa high-pressure gas to completely fill the calcium carbonate resin mold with the slurry; (6) placing the gel mold containing the gel slurry and the calcium carbonate resin mold on a heating platform and keeping it at 30-70°C for 10-60 min. After solidification, the mold is removed to obtain a SiC blank; (7) The SiC body is placed in a dryer and dried at a vacuum degree of 50-250 Pa for 12-24 h to remove moisture; the dried SiC ceramic body is heated to 450-600 °C at a heating rate of 0.1-2 °C / min to degrease and remove resin, wherein the heating rate from 350 °C to 450 °C is 0.1-0.5 °C / min; then the body is heated to 1000-1300 °C at a heating rate of 0.5-5 °C / min for sintering to obtain a body with a certain strength, wherein the heating rate from 650 °C to 750 °C is 0.5-1 °C / min; the sintered body is placed in a prepared 1-5 mol / L hydrochloric acid solution to remove residual calcium oxide to obtain a SiC ceramic green body; (8) The SiC ceramic green body soaked in hydrochloric acid solution is heated to 200-400°C in a box furnace at a heating rate of 1-10°C / min, kept at this temperature for 30-120 min, and then cooled to room temperature at a cooling rate of 2-10°C / min for drying to obtain a SiC ceramic skeleton; then the SiC ceramic skeleton is placed in an alumina crucible, an Al or Al alloy block is placed on the SiC ceramic skeleton, and then the crucible is placed in an infiltration furnace; the infiltration furnace is evacuated to below 50 Pa, heated to 700-850°C at a heating rate of 5-10°C / min, kept at this temperature for 0-30 min, and high-purity argon gas is introduced into the vacuum furnace to 1-5 MPa; then the SiC ceramic green body is cooled to room temperature at a cooling rate of 5-10°C / min, and then liquid metal aluminum is injected into the ceramic skeleton to obtain an Al / SiC composite material with continuous metal distribution; The prepared Al / SiC composite material with continuous metal distribution has continuous distribution of metal Al phase (thickness of 100 μm-1mm), isolated distribution of SiC-rich ceramic columns (cross-sectional size of not less than 500 μm), and SiC columns are composed of Al and SiC particles to form a network structure in which the soft phase surrounds the hard phase and the soft phase interpenetrates each other; the shape of the SiC columns is varied, and its plane figures include but are not limited to circle, rectangle, triangle, star, honeycomb, concave honeycomb, broken line, wave, etc.; the obtained pure aluminum SiC composite material has a bending strength of 290-620 MPa and a fracture work of 5.10-2.45 kJ / m 2 .

[0017] When conducting mechanical property tests, the samples can be cut into 2 mm × 4 mm × 20 mm and polished. Then, the three-point bending strength of the composite material is tested on a universal electronic testing machine (Instron 5689, Instron Corp., USA) with a span of 16 mm and a loading speed of 0.5 mm / min. The bending strength of the composite material is calculated according to the following formula ( ), bending strain ( ) and work of fracture (U):

[0018] Where F is the load (N), L is the span (mm), b is the specimen width (mm), h is the specimen thickness (mm), and D is the indenter displacement (mm). is the work done by the applied load, A is the area of ​​the fracture surface (m 2 ).

[0019] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0020] Embodiment 1: A metal continuously distributed Al / SiC composite material, the preparation method of which specifically comprises the following steps: (1) Using magnetic stirring, resin monomer (40 vol.% 1,6-hexanediol diacrylate, 25 vol.% trimethylolpropane triacrylate), diluent (35 vol.% camphor) and photoinitiator (2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, accounting for 4% of the mass of resin monomer and diluent) were mixed to prepare a light-curing resin. The rotation speed was 300 rpm, the heating temperature was 50 °C, the ball-to-material ratio was 2:1, and the stirring time was 20 min. (2) Calcium carbonate powder (D 50 =7.5 μm), photocurable resin (65 vol.%) and dispersant (BYK111, accounting for 0.5 wt.% of the mass of ceramic powder) were mixed by ball milling to prepare a ceramic slurry with a solid content of 35 vol.%, the ball milling speed was 1200 rpm, the ball-to-material ratio was 2:1, and the ball milling time was 20 min; (3) A cylindrical calcium carbonate resin printing model was designed using modeling software. The cylinder had a diameter of 1.8 mm and a center-to-center spacing of 2 mm. Circular holes with a diameter of approximately half the side length were designed on the top and bottom surfaces. These holes were designed to reserve channels for the slurry to flow into during gel injection molding, thereby forming connections between the columns at the top and bottom. The model was saved as an STL file. The model was then molded into a ceramic green body using digital light processing technology. The process parameters used were: layer thickness 45 μm, first layer exposure intensity 35 mW / cm 2 , first layer exposure time 3.5 s, normal layer exposure intensity 16 mW / cm 2 , the exposure time of the normal layer is 1 s, and the number of the first layer is 3; it is cleaned with an organic solvent divalent ester by ultrasonic cleaning, the cleaning time is 5 min, and the number of times is 2; (4) A planetary ball mill was used to prepare a gel slurry by mixing 45 vol.% SiC, 55 vol.% solvent (of which deionized water accounted for 80 vol.%, gel resin accounted for 20 vol.%, and the volume fraction ratio of N,N-dimethylacrylamide to N,N'-methylenebisacrylamide in the gel resin was 10:1), 0.6 wt.% of the dispersant CMC-Na in the ceramic powder, 0.08 wt.% of the initiator ammonium persulfate in the gel resin, and 3 wt.% of the ceramic powder Al2O3 and MgO (mass ratio was 6:1) to prepare a gel slurry. The rotation speed was 110 rpm and the ball milling time was 12 h. (5) Pour the gel slurry into a custom mold, press the calcium carbonate resin mold into the gel slurry, then place the gel mold in a sealed metal can and evacuate to remove bubbles in the slurry, then introduce 0.3 MPa high-pressure gas to completely fill the calcium carbonate resin mold with the slurry; (6) placing the gel mold containing the gel slurry and the calcium carbonate resin mold on a heating platform, keeping it at about 35 °C for 30 min, and removing the mold after solidification to obtain a SiC body; placing the SiC body in a dryer to remove moisture, and drying it at a vacuum degree of about 100 Pa for 12 h; (7) The dried SiC body is heated to 600 °C at a rate of 0.5 °C / min to remove the resin, wherein the heating rate from 350 °C to 450 °C is 0.2 °C / min; then the body is sintered at a rate of 1 °C / min to 1150 °C to obtain a certain strength, wherein the heating rate from 650 °C to 750 °C is 0.5 °C / min; finally, the sintered body is placed in a prepared 2 mol / L hydrochloric acid solution to remove residual calcium oxide, thereby obtaining a SiC ceramic green body; (8) The SiC ceramic green body soaked in hydrochloric acid solution was heated to 300 °C at 10 °C / min in a box furnace, kept warm for 30 min, then heated to 800 °C at 5 °C / min, kept warm for 10 min, and finally cooled to room temperature at 5 °C / min for drying to obtain a SiC ceramic skeleton; then the SiC ceramic skeleton was placed in an alumina crucible, an Al ingot was placed on top of the SiC ceramic skeleton, and then the crucible was placed in an infiltration furnace; after the infiltration furnace was evacuated to 10 Pa, it was heated to 800 °C at 5 °C / min, kept warm for 10 min, and then high-purity argon was introduced into the vacuum furnace to 3 MPa; after the insulation and pressure were completed, it was cooled to room temperature at 10 °C / min to obtain an Al / SiC composite material with continuous metal distribution.

[0021] The sample was cut into 2 mm × 4 mm × 20 mm and polished, and then the three-point bending strength of the composite material was tested. The span was 16 mm, the loading speed was 0.5 mm / min, the bending strength was measured to be 620 MPa, and the fracture work was 2.45 kJ / m 2 .

[0022] Embodiment 2: A metal continuously distributed Al / SiC composite material, the preparation method of which specifically comprises the following steps: (1) Using magnetic stirring, resin monomer (30 vol.% 1,6-hexanediol diacrylate, 30 vol.% trimethylolpropane triacrylate), diluent (40 vol.% camphene) and photoinitiator (2,4,6-trimethylbenzoyl-diphenylphosphine oxide, accounting for 5% of the mass of resin monomer and diluent) were mixed to prepare a light-curing resin. The rotation speed was 200 rpm, the heating temperature was 45 °C, and the stirring time was 40 min. Calcium carbonate powder (D 50 =7.5 μm), photocurable resin (75 vol.%) and dispersant (BYK111, accounting for 0.8 wt.% of the mass of ceramic powder) were mixed by ball milling to prepare a ceramic slurry with a solid content of 25 vol.%, the ball milling speed was 800 rpm, the ball-to-material ratio was 2:1, and the ball milling time was 40 min; (2) Use modeling software to design a concave honeycomb calcium carbonate resin printing model with a side length of 1.8 mm, a concave angle of 60°, and a spacing of 200 μm, and save it as an STL format file; use digital light processing technology to print the calcium carbonate resin slurry. The process parameters used are: layer thickness 40 μm, first layer exposure intensity 42 mW / cm 2 , first layer exposure time 5 s, normal layer exposure intensity 22 mW / cm 2 , the exposure time of the normal layer is 2 s, and the number of the first layer is 3; it is cleaned with an organic solvent divalent ester by ultrasonic cleaning, the cleaning time is 5 min, and the number of times is 2 times; (3) A planetary ball mill was used to prepare a gel slurry by mixing 25 vol.% SiC, 75 vol.% solvent (of which deionized water accounted for 70 vol.%, gel resin accounted for 30 vol.%, and the volume fraction ratio of N,N-dimethylacrylamide to N,N'-methylenebisacrylamide in the gel resin was 8:1), 0.8 wt.% of the dispersant CMC-Na in the ceramic powder, 0.1 wt.% of the initiator ammonium persulfate in the gel resin, and 5 wt.% of Al2O3 and MgO in the ceramic powder (mass ratio was 8:1) to prepare a gel slurry. The rotation speed was 100 rpm and the ball milling time was 8 h. (4) placing the gel mold containing the gel slurry and the calcium carbonate resin mold on a heating platform, keeping it at about 45 °C for 50 min, and removing the mold after solidification to obtain a SiC body; placing the SiC body in a dryer to remove moisture, and drying it at a vacuum degree of about 100 Pa for 18 h; The other parameters and steps are the same as those in Example 1, and a continuous metal isolated concave honeycomb ceramic-rich Al / SiC composite material is obtained.

[0023] The sample was cut into 2 mm × 4 mm × 20 mm and polished, and then the three-point bending strength of the composite material was tested. The span was 16 mm, the loading speed was 0.5 mm / min, the bending strength was measured to be 290 MPa, and the fracture work was 5.10 kJ / m 2 .

[0024] Embodiment 3: A metal continuously distributed Al / SiC composite material, the preparation method of which specifically comprises the following steps: (1) Using magnetic stirring, resin monomer (30 vol.% 1,6-hexanediol diacrylate, 35 vol.% trimethylolpropane triacrylate), diluent (35 vol.% hydroxyethyl methacrylate) and photoinitiator (2,4,6-trimethylbenzoyl-diphenylphosphine oxide, accounting for 3% of the mass of resin monomer and diluent) were mixed to prepare a light-curing resin. The rotation speed was 200 rpm, the heating temperature was 50 °C, and the stirring time was 30 min. Calcium carbonate powder (D 50 =7.5 μm), photocurable resin (70 vol.%) and dispersant (BYK111, accounting for 1 wt.% of the mass of ceramic powder) were mixed by ball milling to prepare a ceramic slurry with a solid content of 30 vol.%. The ball milling speed was 1200 rpm, the ball-to-material ratio was 2:1, and the ball milling time was 10 min. (2) A zigzag calcium carbonate resin printing model was designed using modeling software. The cylinder diameter was 0.4 mm, the unit spacing was 1 mm, the horizontal overlap was 90°, and the vertical inclination angle was 45°. The model was saved as an STL file. The calcium carbonate resin slurry was printed using digital light processing technology. The process parameters used were: layer thickness 45 μm, first layer exposure intensity 42 mW / cm 2 , first layer exposure time 4 s, normal layer exposure intensity 20 mW / cm 2 , the exposure time of the normal layer is 2.5 s, and the number of the first layer is 3; it is cleaned with an organic solvent divalent ester by ultrasonic cleaning, the cleaning time is 5 min, and the number of times is 2; (3) A planetary ball mill was used to prepare a gel slurry by mixing 35 vol.% SiC, 65 vol.% solvent (of which deionized water accounted for 70 vol.%, gel resin accounted for 30 vol.%, and the volume fraction ratio of N,N-dimethylacrylamide to N,N'-methylenebisacrylamide in the gel resin was 12:1), 0.6 wt.% of the dispersant CMC-Na in the ceramic powder, 0.15 wt.% of the initiator ammonium persulfate in the gel resin, and 8 wt.% of the ceramic powder Al2O3 and MgO (mass ratio was 5:1) to prepare a gel slurry. The rotation speed was 200 rpm and the ball milling time was 15 h. (4) placing the gel mold containing the gel slurry and the calcium carbonate resin mold on a heating platform, keeping it at about 30 °C for 10 min, and removing the mold after solidification to obtain a SiC body; placing the SiC body in a dryer to remove moisture, and drying it at a vacuum degree of about 100 Pa for 14 h; The other parameters and steps are the same as those in Example 1, and a metal-ceramic continuous zigzag Al / SiC composite material is obtained.

[0025] The sample was cut into 2 mm × 4 mm × 20 mm and polished, and then the three-point bending strength of the composite material was tested. The span was 16 mm, the loading speed was 0.5 mm / min, the bending strength was measured to be 452 MPa, and the fracture work was 3.56 kJ / m 2 .

[0026] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An Al / SiC composite material with continuous metal distribution, characterized in that: In the Al / SiC composite material, the metallic Al phase is continuously distributed, and the SiC-rich ceramic pillars are isolatedly distributed; The SiC-rich ceramic pillars are composed of Al and SiC particles, forming a network structure in which the soft phase surrounds the hard phase and the soft phases interpenetrate each other; The plane shape of the SiC-rich ceramic column is one of a circle, a rectangle, a triangle, a star, a honeycomb, a concave honeycomb, a broken line, and a wave; The ceramic volume fraction in the SiC-rich ceramic column is 25-60 vol.%.

2. A method for preparing the Al / SiC composite material with continuous metal distribution as claimed in claim 1, characterized in that: The following steps are involved: (1) preparing a photocurable resin composed of a resin monomer, a diluent and a photoinitiator; wherein, by volume percentage, the resin monomer is 50-65%, the diluent is 35-50%, and the sum of the volume percentages of the resin monomer and the diluent is 100%; and a photoinitiator is additionally added, the amount of which, by mass percentage, accounts for 2-5% of the total mass of the resin monomer and the diluent; (2) mixing calcium carbonate powder, photocurable resin and dispersant by ball milling into a printing slurry; wherein, by volume percentage, the calcium carbonate powder is 20-40%, the photocurable resin is 80-60%, and the sum of the volume percentages of the calcium carbonate powder and the photocurable resin is 100%; and additionally adding a dispersant BYK111, the amount of which by mass percentage accounts for 0.5-1.5% of the calcium carbonate powder; (3) Using modeling software to build a calcium carbonate resin model, using digital light processing technology to print the printing slurry into shape, and using an organic solvent to clean the calcium carbonate resin model to remove excess slurry; (4) preparing a gel slurry formed by ball-milling a SiC ceramic powder, deionized water, an initiator, a gel resin, a sintering aid and a dispersant; wherein, by volume percentage, 20-50% SiC ceramic powder, 80-50% solvent, the sum of the volume percentages of SiC ceramic powder and solvent is 100%, and the solvent comprises 90-60% deionized water and 10-40% gel resin; a sintering aid is additionally added, the amount of which is 1-10% of the SiC ceramic powder by mass percentage; a dispersant is additionally added, the amount of which is 0.2-1.0% of the SiC ceramic powder by mass percentage; an initiator is additionally added, the amount of which is 0.05-0.2% of the gel resin by mass percentage; (5) pouring the gel slurry into a custom mold, pressing the calcium carbonate resin model into the gel slurry, then placing the mold in a sealed metal can and evacuating the can to remove bubbles in the slurry, and then introducing high-pressure gas to completely fill the calcium carbonate resin model with the slurry; (6) placing the mold containing the gel slurry and the calcium carbonate resin model on a heating platform, and removing the mold after the gel is solidified to obtain a SiC blank; (7) drying the solidified SiC body to remove residual moisture, then removing the resin through a degreasing process, and then obtaining a body according to a sintering process, and immersing the body in a hydrochloric acid solution to remove residual calcium oxide, thereby obtaining a SiC isolated column body with continuous pores; (8) The SiC isolated column blank with continuous pores is dried to obtain a SiC ceramic skeleton, into which liquid metal aluminum or aluminum alloy is injected using a pressure infiltration technique to obtain an Al / SiC composite material with continuous metal distribution.

3. The method for preparing the Al / SiC composite material with continuous metal distribution according to claim 2, characterized in that: In step (1), the resin monomer is an acrylate monomer or a vinyl ether monomer; The diluent is one or more of pentaerythritol triacrylate, hydroxyethyl methacrylate, camphene, glycerol, tert-butyl alcohol and camphor; The photoinitiator is one or more of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone and 2-isopropylthioxanthone; The mixing method is heating magnetic stirring, the rotation speed is 100-400 rpm, the heating temperature is 25-50°C, and the stirring time is 20-60 min.

4. The method for preparing the Al / SiC composite material with continuous metal distribution according to claim 2, characterized in that: In step (3), the plane shape of the SiC-rich ceramic column is one of a circle, a rectangle, a triangle, a star, a honeycomb, a concave honeycomb, a broken line, and a wave; The top and bottom surfaces of the calcium carbonate resin model are designed with circular holes for reserving channels for the slurry to flow into during the gel injection molding process, and forming connections between the columns at the top and bottom.

5. The method for preparing the Al / SiC composite material with continuous metal distribution according to claim 2, characterized in that: In step (4), the gel resin is a mixture of N,N-dimethylacrylamide and N,N'-methylenebisacrylamide, and the volume ratio of N,N-dimethylacrylamide to N,N'-methylenebisacrylamide is 6-15:1; The sintering aid is a mixture of Al2O3 and MgO, and the mass ratio of Al2O3 to MgO is 2-8:1; The dispersant is CMC-Na; The initiator is ammonium persulfate.

6. The method for preparing the Al / SiC composite material with continuous metal distribution according to claim 2, characterized in that: In step (6), the curing operation is: keeping the temperature between 30-70° C. on a heating platform for 10-60 min.

7. The method for preparing the Al / SiC composite material with continuous metal distribution according to claim 2, characterized in that: In step (7), the drying operation is: drying in a vacuum drying oven at a vacuum degree of 50-250 Pa for 12-24 h; The degreasing operation is: heating to 450-600°C at a heating rate of 0.1-2°C / min, wherein the heating rate from 350°C to 450°C is 0.1-0.5°C / min; The sintering operation is: heating to 1000-1300°C at a heating rate of 0.5-5°C / min, wherein the heating rate in the stage of heating from 650°C to 750°C is 0.5-1°C / min.

8. The method for preparing the Al / SiC composite material with continuous metal distribution according to claim 2, characterized in that: In step (8), the drying operation is as follows: heating to 200-400°C at a heating rate of 1-10°C / min, keeping the temperature for 30-120min, and then cooling to room temperature at a cooling rate of 2-10°C / min; The pressure infiltration technology is specifically as follows: placing a SiC ceramic skeleton into an alumina crucible, placing an Al or Al alloy block on top of the SiC ceramic skeleton, and then placing the crucible into an infiltration furnace; evacuating the infiltration furnace to below 50 Pa, heating the furnace to 700-850°C at a heating rate of 5-10°C / min, keeping the temperature for 0-30 min, and introducing high-purity argon gas into the vacuum furnace to 1-5 MPa; and then cooling the furnace to room temperature at a cooling rate of 5-10°C / min.

Citation Information

Cited By

  • Printable wax-based sacrificial template and metal-based composite material constructed by using same

    CN120988495A